Robert B. Parker's Damned if you do [large type] : a Jesse Stone novel - Parker, Robert B., 1932-2010 (Parker, Robert B., 1932-2010. Jesse Stone novels., 2013)
Police chief Jesse Stone uncovers a turf war between rival pimps after a young woman is found murdered in a shabby beach motel.